2014
DOI: 10.2308/ajpt-50905
|View full text |Cite
|
Sign up to set email alerts
|

On the Operational Reality of Auditors' Independence: Lessons from the Field

Abstract: SUMMARY Auditor independence, which has certainly been one of the most addressed topics in auditing literature, is a complex and ambiguous construct that can be analyzed along two dimensions. The first dimension, organizational independence, relates to auditors' willingness to act in accordance with professional standards and to report errors found during the audit. The second dimension, operational independence, relates to auditors' capability to work diligently and effectively in order to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(96 citation statements)
references
References 78 publications
6
88
1
1
Order By: Relevance
“…The discourse in CGRs regarding audit committees in the subordination dimensions indicates that audit committees are in a position to pressure auditors in the selection of areas to be included in the audit plan. Here, the findings of the study are in line with Guénin‐Paracini et al () in their argument that auditees may be in a position to control or obstruct auditor access to information. The indications on audit committee involvement in auditor planning give cause for concern regarding auditors' abilities to attain knowledge for the planning and risk analysis without the auditees’ understanding and knowledge, which is a requirement for epistemic independence (Power, ; Scott, ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The discourse in CGRs regarding audit committees in the subordination dimensions indicates that audit committees are in a position to pressure auditors in the selection of areas to be included in the audit plan. Here, the findings of the study are in line with Guénin‐Paracini et al () in their argument that auditees may be in a position to control or obstruct auditor access to information. The indications on audit committee involvement in auditor planning give cause for concern regarding auditors' abilities to attain knowledge for the planning and risk analysis without the auditees’ understanding and knowledge, which is a requirement for epistemic independence (Power, ; Scott, ).…”
Section: Discussionsupporting
confidence: 90%
“…Hellman's study was conducted during 2003–2004 (i.e., before the SwCGC took effect). Hellman () findings align with findings by Guénin‐Paracini et al (, p. 201), who demonstrated that “the smooth conduct of an audit engagement largely depends on the auditees' desire to cooperate.” Catasús, Hellman, and Humphrey () indicated that Swedish audit committees utilize the external auditor in their management of the company. Furthermore, there are indications in several studies that audit committee members are not always as knowledgeable and independent as regulations suggest (cf.…”
Section: Audit Committee Role Regarding Auditor Independencesupporting
confidence: 76%
See 2 more Smart Citations
“…; Guénin‐Paracini et al. ) prior to the AGM. Yet this endpoint has also been described as vulnerable (Pentland ; Power ; Barrett and Gendron ; Smith‐Lacroix et al.…”
Section: Introductionmentioning
confidence: 99%